2020
DOI: 10.1038/s41467-020-16524-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong coupling between nanoparticle plasmons and cavity photons at ambient conditions

Abstract: Ultrastrong coupling is a distinct regime of electromagnetic interaction that enables a rich variety of intriguing physical phenomena. Traditionally, this regime has been reached by coupling intersubband transitions of multiple quantum wells, superconducting artificial atoms, or two-dimensional electron gases to microcavity resonators. However, employing these platforms requires demanding experimental conditions such as cryogenic temperatures, strong magnetic fields, and high vacuum. Here, we use a plasmonic n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 42 publications
(48 reference statements)
6
83
0
Order By: Relevance
“…This results in symmetric and anti-symmetric hybrid eigenmodes with the splitting between the two determined by the thickness of the middle mirror. This view is similar to the symmetric and anti-symmetric polariton branches in the Rabi-like problem, following which, the three-mirror geometries were recently interpreted in terms of hybrid light-matter polaritonic states [31][32][33].…”
Section: Nanoflake Trimerssupporting
confidence: 60%
“…This results in symmetric and anti-symmetric hybrid eigenmodes with the splitting between the two determined by the thickness of the middle mirror. This view is similar to the symmetric and anti-symmetric polariton branches in the Rabi-like problem, following which, the three-mirror geometries were recently interpreted in terms of hybrid light-matter polaritonic states [31][32][33].…”
Section: Nanoflake Trimerssupporting
confidence: 60%
“…Therefore, we employed Au‐Ag alloy NPs with a high oscillator strength and sufficient durability against oxidation reactions [28–31] to construct a photoanode under ultrastrong coupling conditions for efficient photochemical water splitting. From optical measurements, we found that this photoanode presents a splitting energy of up to 620 meV, which can be categorized into the ultrastrong coupling regime [32, 33, 37] . In addition, during photocurrent measurements using this photoanode, only Ag on the surface of the Au‐Ag alloy NPs eluted in the very early stage of the reaction, and a long‐term stable photocurrent was observed.…”
Section: Figurementioning
confidence: 88%
“…This result indicates that the AATA structure fulfils the ultrastrong coupling condition, which is defined as ħΩ>0.2 ħω 0, as discussed for both modal and light‐matter coupling. [ 32 , 37 ] Figures 2 b and 2c show the absorption and incident photon‐to‐current efficiency (IPCE) action spectra of the AATA and ATA photoanodes. Before starting the IPCE measurement, the photoanodes were irradiated with 580 nm light for 2 hours to remove Ag from the surface of the Au‐Ag alloy NPs.…”
mentioning
confidence: 99%
“…In very recent studies, the combination of plasmonic nanostructures and photonic dielectrics has led to a good balance between confinement and absorption loss. [ 81–89 ] As such, enhanced light‐matter interactions sit at the core of hybrid optoplasmonic systems for the development of novel nanophotonic devices for sensing, light emission, and information processing, etc. [ 81,83,87,89 ] Photonic crystals, Fabry–Pérot cavities, photonic waveguides, and optical fibers have been integrated with plasmonic nanostructures, previously.…”
Section: Configurations and Fabricationsmentioning
confidence: 99%